1967
DOI: 10.1029/jz072i024p06371
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of seven lightning discharges that caused forest fires

Abstract: The hypothesis that lightning fires are caused by a special type of lightning discharge has been presented several times in literature over the past 20 years. Working with laboratory sparks, McEachron and Hagenguth [1942] suggested that ignition by natural lightning is usually caused by a discharge having a long‐continuing current phase. This view is widely accepted [Berger, 1947; Malan, 1963; Loeb, 1966], even though field corroboration has been almost nil. To the authors' knowledge, the two discharges and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 3 publications
4
56
1
1
Order By: Relevance
“…Complementary to the postfire investigations, the analysis of remotely sensed data presented here demonstrates a high risk of fire ignition from lightning in that region, including due to the high concentration of lightning activity produced by the Kinglake pyroCb in the region where this new fire occurred (Figure ). Another important factor in determining whether or not a sustained fire will develop following a lightning ignition is the amount of precipitation that accompanies the lightning activity, with lightning accompanied by relatively little precipitation known as dry lightning [ Fuquay et al , ; Latham , ; Rorig and Ferguson , ]. The risk of fire occurrence from a lightning ignition in this region of southeast Australia is higher than average if less than about 3 mm of precipitation occurs and lower than average if more than about 5 mm of precipitation occurs [ Dowdy and Mills , , ].…”
Section: Resultsmentioning
confidence: 99%
“…Complementary to the postfire investigations, the analysis of remotely sensed data presented here demonstrates a high risk of fire ignition from lightning in that region, including due to the high concentration of lightning activity produced by the Kinglake pyroCb in the region where this new fire occurred (Figure ). Another important factor in determining whether or not a sustained fire will develop following a lightning ignition is the amount of precipitation that accompanies the lightning activity, with lightning accompanied by relatively little precipitation known as dry lightning [ Fuquay et al , ; Latham , ; Rorig and Ferguson , ]. The risk of fire occurrence from a lightning ignition in this region of southeast Australia is higher than average if less than about 3 mm of precipitation occurs and lower than average if more than about 5 mm of precipitation occurs [ Dowdy and Mills , , ].…”
Section: Resultsmentioning
confidence: 99%
“…The solid dashed line represents the region of convergence along the Olt River, where convection is often initiated. than negative flashes (e.g., Nakahori et al 1982;Idone et al 1984) and are also more likely to start forest fires (e.g., Fuquay et al 1967;Rakov and Uman 2003). Fig.…”
Section: Positive Cloud-to-ground Lightning Densitymentioning
confidence: 99%
“…The efficiency of individual lightning strikes in igniting a forest fire is mainly affected by the variety in lightning properties such as the quantity, polarity and intensity [5]. Research has shown that the long-continuing current intensity of a lightning discharge is responsible for most, if not all, lightning-caused fires [8][9][10]. The advent of lightning location systems has advanced lightning-caused fire prediction [11][12][13].…”
Section: Introductionmentioning
confidence: 99%